2020
DOI: 10.1177/0734242x20941085
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and composition identification of waste-derived fuels obtained from municipal solid waste using thermogravimetry: A review

Abstract: Thermogravimetric analysis (TGA) is the most widespread thermal analytical technique applied to waste materials. By way of critical review, we establish a theoretical framework for the use of TGA under non-isothermal conditions for compositional analysis of waste-derived fuels from municipal solid waste (MSW) (solid recovered fuel (SRF), or refuse-derived fuel (RDF)). Thermal behaviour of SRF/RDF is described as a complex mixture of several components at multiple levels (including an assembly of prevalent wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 202 publications
(343 reference statements)
0
22
0
Order By: Relevance
“…Comparing Subcoal™ PAF results in TGA to the literature, Gerassimidou et al, in 2020, found the N 2 pyrolysis of SRF T m = 500 • C and for paper waste T m = 575 • C, at 20 • C/min. In addition, the pyrolysis results of paperboard show T m = 732 • C, while the oxidation of SRF results show T m = 600 • C. This result proves that thermal degradation of Subcoal™ pyrolysis and oxidation is lower than SRF, paper waste, and paperboard [25].…”
Section: Thermal Parametersmentioning
confidence: 68%
“…Comparing Subcoal™ PAF results in TGA to the literature, Gerassimidou et al, in 2020, found the N 2 pyrolysis of SRF T m = 500 • C and for paper waste T m = 575 • C, at 20 • C/min. In addition, the pyrolysis results of paperboard show T m = 732 • C, while the oxidation of SRF results show T m = 600 • C. This result proves that thermal degradation of Subcoal™ pyrolysis and oxidation is lower than SRF, paper waste, and paperboard [25].…”
Section: Thermal Parametersmentioning
confidence: 68%
“…Table 2 shows a summary of the thermal character data of ramie by comparing the weight loss and DTG data with other natural fibers. The thermogravimetric behaviour of natural fiber has a three-stage thermal decomposition (Stage I is frying stage, Stage II is active pyrolysis stage, and stage III is passive pyrolysis stage) pattern and other plant polymer characters by providing a degradation ratio of the cellulose fraction in the range of 200–400 °C [ 28 ]. Moreover, weight loss in the first stage is the process of losing water content in the fiber, while the thermal degradation associated with the lignocellulosic structure begins at the second decomposition stage.…”
Section: Resultsmentioning
confidence: 99%
“…It was established that fuel substitution resulted in maximum co-benefits of reduced cost and CO 2 emissions, while a major concern considered for RDF is to meet limits of chlorine (Cl) content. Gerassimidou et al [37] reviewed thermogravimetric characterization of RDF and concluded there is high potential to develop TGA-based composition identification. Yang et al [38] conducted a review on RDF gasification and recorded the production cost of energy estimated at 0.05 USD/kWh.…”
Section: Introductionmentioning
confidence: 99%